2015
DOI: 10.7314/apjcp.2015.16.8.3493
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Codon 72 Polymorphisms and Lung Cancer Risk in the Bangladeshi Population

Abstract: Objective: To assess associations between codon 72 polymorphisms (Pro or B and Arg or b alleles) of the TP53 gene and lung cancer risk among Bangladeshis. Materials and Methods: The distribution of the BB, Bb, and bb genotypes and the frequencies of the B and b alleles were determined by PCR-RFLP method using DNA extracted from leucocytes of 50 confirmed lung cancer patients and 50 age-matched controls and the data were analysed. Results: The ratio of BB, Bb, and bb genotypes were in Hardy-Weinberg equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…A total of 12 case-control studies were included in this meta-analysis to find out the association of TP53 codon 72 Arg/Pro polymorphism with lung cancer and breast cancer in the South Asian population based on the inclusion criteria (Shabnaz et al, 2016;Hashemi et al, 2018;Aziz et al, 2013;Suresh et al, 2011;Syeed et al, 2010;Ihsan et al, 2011;Tilak et al, 2013;Chowdhury et al, 2015;Mostaid et al, 2014;Saikia et al, 2014;Sharma et al, 2014). Among these, six studies evaluated the association for breast cancer (950 cases and 882 controls) and the other six studies for lung cancer (975 cases and 1,397 controls).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A total of 12 case-control studies were included in this meta-analysis to find out the association of TP53 codon 72 Arg/Pro polymorphism with lung cancer and breast cancer in the South Asian population based on the inclusion criteria (Shabnaz et al, 2016;Hashemi et al, 2018;Aziz et al, 2013;Suresh et al, 2011;Syeed et al, 2010;Ihsan et al, 2011;Tilak et al, 2013;Chowdhury et al, 2015;Mostaid et al, 2014;Saikia et al, 2014;Sharma et al, 2014). Among these, six studies evaluated the association for breast cancer (950 cases and 882 controls) and the other six studies for lung cancer (975 cases and 1,397 controls).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…They found that rs1042522 C>G polymorphism conferred higher susceptibility to thyroid cancer [39]. In a study conducted among the Bangladeshi population including 50 histopatho-logically confirmed lung cancer patients and 50 age-matched controls, Chowdhury et al found that the TP53 gene rs1042522 CC genotype is a risk factor for lung cancer [40]. Wu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al have reported that smokers with Pro/Pro genotype had a 2.00-fold increased risk of hepatocellular carcinoma in a Chinese population when compared with non-smoking individuals with Arg/Arg genotype (26). In a population in Bangladesh, it has been reported that TP53Pro allele as a risk factor for lung cancer overrepresented among smokers compared to controls (OR = 1.8 -10.0, P ≤ 0.01 -0.03) (27). On the other hand, a significant interaction has been reported between TP53 Pro/Pro genetic polymorphism and smoking in esophageal squamous cell carcinoma (OR = 5.29, 95% CI = 2.91 -9.61) (28).…”
Section: Discussionmentioning
confidence: 99%